Solution properties of poly(amic acid)-NMP containing LiCl and their effects on membrane morphologies - Lee, HJ; Won, J; Lee, H; Kang, YS (ELSEVIER SCIENCE BV, 2002)
Physical properties of poly(amic acid) (PAA) casting solutions in N-methyl-2-pyrrolidone (NMP) containing lithium chloride (LiCl) were characterized by viscometry and dynamic light scattering (DLS) and were related to the morphological properties of asymmetric membranes prepared from these solutions. At a fixed polymer concentration, the increase in viscosity of the PAA solutions with increasing LiCl content is mainly determined by the viscosity of the salt-solvent medium, implying that the LiCl-NMP interactions are stronger than those between LiCl and PAA. Because of the strong salt-solvent interactions, complexes b.-tween LiCl and NMP are formed. The complexes reduce the solvent power of NMP for PAA inducing polymer aggregation (clustering) and/or transient cross-links in the solutions. Dynamic light scattering results for salt-containing solutions at low PAA concentrations support the existence of these aggregations. Solutions without salt showed a single relaxation, but solutions with LiCl exhibit multiple relaxation modes; two diffusional modes of cooperative and aggregates, and one angle independent transient network mode. The polymer aggregates and transient cross-links form a gel-like structure in the casting solution film and hinder macrovoid formation during phase inversion, resulting in asymmetric membranes with a primarily sponge-like structure. (C) 2002 Elsevier Science B.V. All rights reserved.
Keywords: DYNAMIC LIGHT-SCATTERING; DOPE SOLUTION CHARACTERISTICS; SEMIDILUTE POLYMER-SOLUTIONS; GAS-TRANSPORT PROPERTIES; THREAD-LIKE MICELLES; ETHYL-ACETATE; LITHIUM-CHLORIDE; BEHAVIOR; CELLULOSE; SYSTEM